Pendidikan Seks Anak dalam Mengantisipasi Perilaku LBGT - Rianawati Rianawati (Raheema, 2016)
Nowadays, the education world challenges a great issue regarding Lesbian, Gay, Bisexual, and Transgender (LGBT). Thus, parental and formal educations have significant effect to anticipate these problems through early sex education. Furthermore, sex education is an effort performed by parents and teachers to create positive behaviors towards children about sex and gender whether generally or based on Islam point of view. As a result, the goal of sex education is children could avoid – socially and morally – the negative behavior of sexual disorders in the future.